Perioperative Management of Diabetes: A Review (Delta Medical College Journal, 2014)
Diabetes increases the requirements of surgery as well as perioperative morbidity and mortality. Careful preoperative evaluation and treatment of cardiac and renal diseases, intensive intraoperative and postoperative management are essential to optimize the best outcome. Stress hyperglycemia in response to surgery, osmotic diuresis and hypoinsulinemia can lead to life threatening complications like ketoacidosis or hyperglycemic hyperosmolar syndrome. Wound healing is impaired by hyperglycemia and chance of postoperative wound infection is more in diabetics. Therefore aseptic precautions must be taken. Adequate insulin, glucose, fluid and electrolytes should be provided for good metabolic control. Though some current study reveals that oral hypoglycemic agents can be used for the effective management of perioperative diabetes; the adverse effects of newly introduced agents need more clinical observations. Subcutaneous administration of insulin as in Sliding Scale may be a less preferable method, because of unreliable absorption and unpredictable blood glucose. Intravenous administration of rapid onset soluble (short acting) insulin as in Alberti (GIK) regimen, is safe and effective method controlling perioperative hyperglycemia. Patient with type 1 diabetes needs frequent monitoring of glucose, electrolytes and acid-base balance as chance of high hyperglycemia and ketoacidosis is more. In case of emergency surgery assessment for diabetic ketoacidosis (DKA) and meticulous management is essential. Postoperative pain and hyperglycemia should be treated carefully to avoid complications. DOI: http://dx.doi.org/10.3329/dmcj.v2i2.20528 Delta Med Col J. Jul 2014; 2(2): 71-76